Relatos con-fin-a-dos de una «cuarentena» en casa: The Spanish audiovisual production with smartphone during the Covid-19 pandemic era - Macarro, Jordi (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2021)
The recent COVID-19 pandemic has hit the world hard. During the months in which the individual and collective freedoms were modified by the preventive restrictions due to the advance of this new microscopic agent, the Spanish audiovisual production adapted to the new conditions of quarantine and confinement. The smartphone became the democratised tool that allowed people to tell their daily reality, and would soon become the content on which the stories of a «new normality» were to be structured. This article is a first approach to the method of representation and the treatment given to this sanitary vector through three Spanish series.